PENGGUNAAN MEDIA POWER POINT UNTUK MENINGKATKAN HASIL BELAJAR REPRODUKSI TUMBUHAN PADA PESERTA DIDIK KELAS XII ATP 2 SMKN 1 PASIR PENYU - Heru Joedo Prasetyo (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to increase the activities of learners, especially in the reproductive competence of plants where inthe learning process of students in the group directed to follow the appropriate learning steps. This research wasconducted on students of class XII ATP 2 SMKN 1 Pasir Penyu, as many as 29 people. In cycle 1 shows that afterthe learning action through the use of power point media was 73.52% complete learners learn, absorption 83.39%,100% material completeness and learner activity is in less active category. In cycle 2 shows students' learningmastery of 76.47%, absorption 86.04%, 100% material exhaustiveness and learner activity exist in fairly activecategory. From the results of this study showed that after the learning action through the use of power point media,it turns out the activities and learning outcomes of learners in the reproductive competence of plants from cycle 1and cycle 2 increased significantly.